2010
DOI: 10.1007/s11242-010-9583-y
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of Natural Convection in an Enclosure Filled with Disconnected Conducting Square Solid Blocks

Abstract: Two different approaches have been implemented to interpret the existing data in Merrikh and Lage (2005a, in: Pop, Ingham, Transport Phenomena in Porous Media, Elsevier, Oxford) pertinent to the pore-scale simulation of natural convection in a laterally heated square enclosure filled with a fluid bathing discrete, disconnected and conducting solid blocks. Mathematical analysis of the problem based on the least squares method leads us to a Nu-Ra correlation with the solid-to-fluid thermal conductivity ratio an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Using the least squares method to curve-fit numerical simulation results, similar to Hooman and Merrikh [35], an estimate for Nu tot as a function of Rayleigh number (10 4 ≤ Ra ≤ 10 7 ) and number of the coolers (1 ≤ N ≤ 3) is given by:…”
Section: Number Of the Coolermentioning
confidence: 99%
“…Using the least squares method to curve-fit numerical simulation results, similar to Hooman and Merrikh [35], an estimate for Nu tot as a function of Rayleigh number (10 4 ≤ Ra ≤ 10 7 ) and number of the coolers (1 ≤ N ≤ 3) is given by:…”
Section: Number Of the Coolermentioning
confidence: 99%
“…Using the least squares method to curve-fit numerical simulation results, similar to Hooman and Merrikh [34], an estimate for Nu tot as a function of Rayleigh number (10 4 6 Ra 6 10 7 ) and number of the HACs (1 6 N 6 3) can be found:…”
Section: The Effects Of Number Of Hacsmentioning
confidence: 99%
“…Typical examples in this category are the works by Das and Reddy [2006], Desrayaud and Lauriat [2001], Laaroussi and Lauriat [2008] and Yoon et al [2010], all of which are limited to steady state two dimensional laminar natural convection flow of Rayleigh number ranging from 10⁵ to 10⁸. Das and Reddy [2006] and Yoon et al [2010] have reported the fluid flow and heat transfer in a differentially heated rectangular cavity containing just one disconnected solid product, and de Lemos [2005a and2005b] and Hooman and Merrikh [2010] investigated the cavity filled with several. The findings from these research works show that when a limited number of solid products are involved, the fluid flow is predominantly confined between the vertical walls and the first column of the objects.…”
Section: Natural Convection In Cavity Filled By Solid Productsmentioning
confidence: 99%